Time analysis for the IAAF World Championships London 2017 800 m Women's - Hanley, B.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s 800 m final was held in the late evening of August 13th. The heats were held three days earlier on August 10th, with the semi-finals the following evening. In the six heats, the first three finishers qualified automatically, and the six fastest non-automatic qualifiers also progressed. There were three semi-finals; the first two in each qualified for the final automatically, along with the two fastest losers. The average speeds for each athlete over every 100 m segment are included in this report, as well as a graph of each athlete`s position at each 100 m split. The split data were provided by SEIKO. The results of the final are shown below. (Attention! registration on the IAAF site is required for downloading)